DYNAMIC MORPHOLOGICAL CHANGES IN THE STOMACH IN THE CONTEXT OF ULCERATIVE COLITIS: AN EXPERIMENTAL STUDY - Vohidov Bekzod Rafiq o’g’li (TADQIQOTLAR, 2025)
Abstract This study comprehensively examined morphological and morphometric changes in the gastric mucosa and wall under experimental ulcerative colitis (UC) conditions. The experiment was conducted using an animal model in which colitis was induced with TNBS. Histological examinations revealed severe dystrophic, inflammatory, erosive, and necrotic changes in the gastric mucosa, vascular and cellular infiltration in the submucosa, and degenerative processes in the muscular layer. These changes significantly impact the structural and functional state of the gastric wall. The results have practical significance for clinical gastroenterology and morphology.